THE DEVELOPMENT OF CONCEPTUAL-CONFLICT-BASED LEARNING DEVICE IN MATHEMATICAL PROBLEM SOLVING - Andi Ika Prasasti Abrar; Andi Dian Angriani; Andi Halimah; Fitriani Nur (MaPan : Jurnal Matematika dan Pembelajaran, 2019)
Abstract:This study aimed to develop conceptual-conflict-based learning device in mathematical problem solving on the subject of equations in three variables systems in the class X at MIA MAN 1 Makassar which was valid, practical and effective. The type of this study was research and development which consisted of: Lesson Plans, Student Book, Student Worksheet, and Learning Outcomes Test. The developmental model used was 4D model which consisted of difining, designing, developing and disseminating. The result of this study obtained that learning device was valid criteria based on the assessment from two validators. While the result of the limited trial showed the learning device was practical, but there were still several suggestions from observers that need to be considered to improve the practicality of the device. It was also effective which was proved by the completeness of learning outcomes that has been achieved, students’ activity was as expected, the ability of teachers to manage the learning was in a high category and the students’ responses was in a positive category.Abstrak:Penelitian ini bertujuan menghasilkan perangkat pembelajaran matematika berbasis konflik konseptual dalam pemecahan masalah pada pokok bahasan sistem persamaan linear tiga variabel kelas X MIA MAN 1 Makassar yang valid, praktis dan efektif. Jenis penelitian ini adalah penelitian dan pengembangan yang terdiri atas: Rencana Pelaksanaan Pembelajaran, Buku Siswa, Lembar Kerja Peserta Didik, dan Tes Hasil Belajar. Model pengembangan yang digunakan adalah model 4D yang terdiri dari tahapan perancangan, pendefinisian, pengembangan dan penyebaran. Hasil penelitian yang diperoleh adalah perangkat pembelajaran memenuhi kriteria valid berdasarkan penilaian oleh dua orang validator. Sedangkan hasil yang diperoleh pada uji coba terbatas, yaitu perangkat pembelajaran sudah praktis, tetapi masih ada beberapa saran pengamat yang perlu diperhatikan untuk meningkatkan kepraktisan perangkat. Perangkat pembelajaran sudah efektif dilihat dari ketuntasan hasil belajar yang telah tercapai, aktivitas siswa sudah sesuai yang diharapkan, kemampuan guru mengelola pembelajaran sudah dalam kategori tinggi dan respon siswa sudah dalam kategori positif.